Gost Gojsav, „poglaviti krstjanin“ in Kosača local administration and the question of patronage of the Radosav’s code - Dautović, Dženan (Historical Thought, 2025)
The Involvement of members of the Bosnian church in social life of their time has long drawn the attention of researchers of medieval Bosnia. It is expected that respected medievists discovered a rare and interesting case of a legal dispute where a central role was taken up by a member of the hierarchy of Bosnian church - gost Gojsav. However this case has led to several different interpretations of the original source material first published by Mihailo Dinic in the third tome of his acclaimed collection of sources. In this paper we will start with the presentation of the entire incident meaning the events where Gojsav took part in, based on the sources of Dubrovnik provenance. Next we present the differing historiographical interpretations of these sources and finish the first part with our own solution to these dilemmas. The second part is dedicated to an untested theory of equating gost Gojsav with a namesake who commisioned the church codex of krstjan Radosav.